ANALYSIS OF KINEMATIC DIAGRAMS OF EXISTING PUMPING UNITS - Grudz, V. Ya.; Grudz, Ya. V.; Bevz, V. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The kinematic schemes of the installations of oil well equipment for oil production are considered, the estimation of their efficiency is given, the efforts on the structural elements in the process of its operation are analyzed. On the basis of the analysis of designs of hydraulic drive rod pump units it is shown that any hydraulic drive rod unit can be considered as a set of several functional blocks, of which the unit of the body organ that carries out the movement of the column of the rod, the block of the hydraulic drive that converts the energy of the energy units is mandatory. drive into the fluid flow of the working fluid and the block system of reversing the flow of the working fluid. It is proved that all installations that use for oil extraction have significant disadvantages, which in this design can not be eliminated, because improvement of one defect leads to deterioration of its other parameters. As a prototype in the design of a new installation, the most advanced designs were taken, and in order to create a new design a complete analysis of each of them was made, a design was selected that has improved characteristics in comparison with the others and will serve to take into account and eliminate the defects that must be taken into account in the design. The technical task of creating a new design is to increase the reliability of the drive, simplify the system of load compensation, eliminate leakage of working fluid and increase the efficiency of the deep-pumping equipment. The analysis of the workflow of the installation made it possible to evaluate the efficiency of operation, which is important in the design of the equipment, in order to improve the reliability of its operation in specific conditions and to reduce energy consumption, ie increase the efficiency of the system.